International liquid biopsy standardization alliance white paper. (December 2020) - Connors, Dana; Allen, Jeff; Alvarez, J.D.; Boyle, Jennifer; Cristofanilli, Massimo; Hiller, Carolyn; Keating, Susan; Kelloff, Gary; Leiman, Lauren; McCormack, Robert; Merino, Diana; Morgan, Emily; et al.
Abstract: The promise of precision medicine as a model to customize health care to the individual patient is heavily dependent upon new genetic tools to classify and characterize diseases and their hosts. Liquid biopsies serve as a safe alternative to solid biopsies and are thus a useful and critical component to fully realizing personalized medicine. The International Liquid Biopsy Standardization Alliance (ILSA) comprises organizations and foundations that recognize the importance of working towards the global use of liquid biopsy in oncology practice to support clinical decision making and regulatory considerations and seek to promote it in their communities. This manuscript provides an overview of the independent liquid biopsy- and standardization-based programs engaged with ILSA, their objectives and progress to date, and the tools and resources each is developing to contribute to the field. It also describes the unique areas of effort as well as synergy found within the group.